Penggunaan Kartu Blocks Pallete Terintegrasi Game Scratch untuk Memperkenalkan Konsep Pemrograman Secara Visual dan Interaktif pada Mata Pelajaran Informatika Kelas X Akuntansi 3 - Widyaskumara, Deta Dyan; Perdana, Devi Maha; Sekartadji, Dewi Indah; Rohmawati, Endah Puji (Universitas Nusantara PGRI Kediri, 2025)
The lack of basic programming comprehension among non-ICT vocational students, particularly in Accounting majors, presents a significant challenge in Informatics education. Most students have not been systematically introduced to programming logic at the junior high school level, resulting in difficulties understanding key concepts such as variables, conditionals, and loops. This study aims to introduce fundamental programming concepts visually and interactively to Grade X Accounting 3 students through the use of Blocks Palette cards within a Project-Based Learning (PjBL) framework. Employing a descriptive qualitative method, data were collected through observations, interviews, surveys, and documentation of student project outcomes. The research subjects consisted of 36 students from a vocational high school. The findings revealed that the use of Blocks Palette cards significantly enhanced students' understanding of programming logic. Prior to the intervention, only 16.7% of students had any exposure to programming, but post-intervention, 83% were able to grasp programming logic sequentially. Moreover, students demonstrated increased motivation and a reduction in errors when arranging Scratch blocks. The integration of card-based media within the PjBL approach proved effective in fostering active, collaborative, and contextual learning environments, in line with Dual Coding Theory and constructivist principles. Therefore, this approach not only improved theoretical understanding but also strengthened practical skills, creativity, and students’ learning motivation.